Subsequent monitoring of ferric ion and ascorbic acid using graphdiyne quantum dots-based optical sensors - Bai, Qiang; Zhang, Chaoyang; Li, Long; Zhu, Zhiling; Wang, Lina; Jiang, Fuyi; Liu, Manhong; Wang, Zhaobo; Yu, William W.; Du, Fanglin; Yang, Zhugen; Sui, Ning (Springer, 2020)
Graphdiyne (GDY) as an emerging carbon nanomaterial has attracted increasing attention because of its uniformly distributed pores, highly π-conjugated, and tunable electronic properties. These excellent characteristics have been widely explored in the fields of energy storage and catalysts, yet there is no report on the development of sensors based on the outstanding optical property of GDY. In this paper, a new sensing mechanism is reported built upon the synergistic effect between inner filter effect and photoinduced electron transfer. We constructed a novel nanosensor based upon the newly-synthesized nanomaterial and demonstrated a sensitive and selective detection for both Fe3+ ion and ascorbic acid, enabling the measurements in real clinical samples. For the first time fluorescent graphdiyne oxide quantum dots (GDYO-QDs) were prepared using a facile ultrasonic protocol and they were characterized with a range of techniques, showing a strong blue-green emission with 14.6% quantum yield. The emission is quenched efficiently by Fe3+ and recovered by ascorbic acid (AA). We have fabricated an off/on fluorescent nanosensors based on this unique property. The nanosensors are able to detect Fe3+ as low as 95 nmol L−1 with a promising dynamic range from 0.25 to 200 μmol L−1. The LOD of AA was 2.5 μmol L−1, with range of 10–500 μmol L−1. It showed a promising capability to detect Fe3+ and AA in serum samples.
Keywords: fluorescence; quenching; graphdiyne; quantum dots; Fe3+; ascorbic acid